Biodiversity and Ethnobotanical Study of Medicinal Plants in the Jageshwar Region, Almora District - Diksha Bairwan; Suresh Chaubey; R.C. Tiwari; Asheesh Pandey (International Journal of Ayurveda and Pharma Research, 2025)
Jageshwar, located in the Almora district of Uttarakhand, India, is renowned for its ancient temple complex and dense forests dominated by Deodar trees (Cedrus deodara), locally called 'Devdaru'. This study aims to identify, document, and promote the conservation of ethnomedicinal plants traditionally used by the local communities in this Himalayan region. Through extensive field surveys and ethnobotanical interviews, the research documents the indigenous knowledge associated with 20 medicinal plant species used to treat a variety of ailments. Key species identified include Vinca major, Trachyspermum sprague, Berberis aristata and Rhododendron arboreum. These plants are employed in the treatment of common illnesses such as cough, cold, fever, and skin infections, as well as chronic conditions like diabetes, asthma, and gastrointestinal disorders. The study not only highlights the therapeutic potential of these plants but also emphasizes the critical role traditional knowledge plays in sustaining primary healthcare in remote areas. Observations indicate a decline in plant availability due to deforestation, climate change, and increasing human activities. The ecological richness of the region, coupled with the cultural significance of its plant-based healing practices, underscores the urgent need for conservation efforts. The study advocates for sustainable forest management, afforestation programs, and responsible tourism to protect this fragile ecosystem. Moreover, it calls for further pharmacological research to validate the efficacy and safety of the documented traditional remedies.